'I'm not your mother': British social realism, neoliberalism and the maternal subject in Sally Wainwright's Happy Valley (BBC1, 2014–2016). (August 2019) - Thornham, Sue
This article examines Sally Wainwright's Happy Valley (BBC1, 2014–2016) in the context of recent feminist attempts to theorise the idea of a maternal subject. Happy Valley, a police series set in an economically disadvantaged community in West Yorkshire, has been seen as expanding the genre of British social realism, in its focus on strong Northern women, by giving it 'a female voice' (Gorton, 2016: 73). I argue that its challenge is more substantial. Both the tradition of British social realism on which the series draws, and the neoliberal narratives of the family which formed the discursive context of its production, I argue, are founded on a social imaginary in which the mother is seen as responsible for the production of the selves of others, but cannot herself be a subject. The series itself, however, places at its centre an active, articulate, mobile and angry maternal subject . In so doing, it radically contests both a tradition of British social realism rooted in male nostalgia and more recent neoliberal narratives of maternal guilt and lifestyle choice. It does this through a more fundamental contestation: of the wider cultural narratives about selfhood and the maternal that underpin both. Its reflective maternal subject, whose narrative journey involves acceptance of an irrecoverable loss, anger and guilt as a crucial aspect of subjectivity, and who embodies an ethics of relationality, is a figure impossible in conventional accounts of subject and nation. She can be understood, however, in terms of recent feminist theories of the maternal.